2015
DOI: 10.1097/mop.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Controlling acute rheumatic fever and rheumatic heart disease in developing countries

Abstract: Reduction in the disease burden and national costs of ARF and RHD are major priorities. New initiatives in the primary and secondary prevention of ARF/RHD, novel developments in pathogenesis and biomarker research and steady progress in vaccine development, are all causes for optimism for improving control of ARF/RHD, which affect the poorest of the poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…1 As RHD affects the poorest people of the world, they often fail to receive the attention they require.7 The global burden of RHD varies according to various regions with unreliable estimates due to missing data in many countries and the use of different methods for diagnosis. 2 Few studies reported, more so only in and around Kathmandu valley to estimate the incidence and prevalence of RHD in Nepalese children. Although the prevalence was initially estimated to be 1 to 1.3/1000 in school children, presence of subclinical carditis in normal children results in much higher prevalence of RHD in the population.…”
Section: Discussionmentioning
confidence: 99%
“…1 As RHD affects the poorest people of the world, they often fail to receive the attention they require.7 The global burden of RHD varies according to various regions with unreliable estimates due to missing data in many countries and the use of different methods for diagnosis. 2 Few studies reported, more so only in and around Kathmandu valley to estimate the incidence and prevalence of RHD in Nepalese children. Although the prevalence was initially estimated to be 1 to 1.3/1000 in school children, presence of subclinical carditis in normal children results in much higher prevalence of RHD in the population.…”
Section: Discussionmentioning
confidence: 99%
“…A review of recent studies predominantly using echocardiography for diagnosis of chronic RHD shows wide global variations in prevalence, between 46 per 100 000 in northern India and 2400 per 100 000 in the Solomon Islands 8. The natural history of RHD has been examined in Indigenous Australians showing that 35% with a first episode of ARF developed RHD by 1 year, 51% by 5 years and 61% by 10 years 5.…”
Section: Rheumatic Heart Diseasementioning
confidence: 99%
“…13 Recent advances and improvements in the early detection, evaluation, and treatment of acute Group A streptococcal pharyngitis has made the prevention and control of RHD feasible in many LMICs. 4 Point-of-care antigen diagnostic testing that provide confirmatory results without the need for bacterial culture and relatively uncomplicated clinical practice guidelines for definitive treatment are now available. 4 The combination of primary prevention and long-term secondary prophylaxis strategies also makes the prevention and eradication of rheumatic heart disease (RHD) possible.…”
Section: Introductionmentioning
confidence: 99%
“…4 Point-of-care antigen diagnostic testing that provide confirmatory results without the need for bacterial culture and relatively uncomplicated clinical practice guidelines for definitive treatment are now available. 4 The combination of primary prevention and long-term secondary prophylaxis strategies also makes the prevention and eradication of rheumatic heart disease (RHD) possible. However, sustained effective implementation, scale-up, and spread of these strategies have not occurred in many low-resource settings in LMICs leading to a continuing high burden of RHD.…”
Section: Introductionmentioning
confidence: 99%